2014
DOI: 10.1002/clen.201300143
|View full text |Cite
|
Sign up to set email alerts
|

Cassava Starch Based Superabsorbent Polymer as Soil Conditioner: Impact on Soil Physico‐Chemical and Biological Properties and Plant Growth

Abstract: Superabsorbent polymers (SAPs) are macromolecules with the ability to absorb water and release it slowly to the surroundings. SAP hydrogels can be used as soil moisture conditioners which act as water reservoirs and release water depending upon the need of plant roots. In the present study, a cassava starch based superabsorbent hydrogel was evaluated as a soil conditioner and its effect on physical, chemical, and biological properties of the soil as well as on plant growth parameters was studied. Amendment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Those polymer absorbents can quickly absorb significant amounts of water, which is subsequently gradually released and thus made available to root systems, mitigating the drought stress in plants . Previous results indicate that hydrogel amendment can result in better plant establishment and growth through improvement in nutrient availability and moisture retention, which is highly relevant under the prevailing global climate change . Studies considering hydrogel application on ornamental plants are scarce, and are limited to the examination of Eucalyptus , Pinus halepensis , Cupresus arizonica , Picea abies , P. sylivestris , and Fagus sylvatica .…”
Section: Introductionmentioning
confidence: 99%
“…Those polymer absorbents can quickly absorb significant amounts of water, which is subsequently gradually released and thus made available to root systems, mitigating the drought stress in plants . Previous results indicate that hydrogel amendment can result in better plant establishment and growth through improvement in nutrient availability and moisture retention, which is highly relevant under the prevailing global climate change . Studies considering hydrogel application on ornamental plants are scarce, and are limited to the examination of Eucalyptus , Pinus halepensis , Cupresus arizonica , Picea abies , P. sylivestris , and Fagus sylvatica .…”
Section: Introductionmentioning
confidence: 99%
“…molar ratio ≥ 0.70) is required to achieve optimum swelling, which is consistent with the high ratio of monomer to starch in their hydrogel samples. In those few studies that observed similar trends to this study, the hydrogels were prepared via conventional solutionbased techniques (Jyothi Alummoottil et al, 2010;Parvathy et al, 2014;Witono et al, 2014).…”
Section: Effect Of Saponification On Swellingsupporting
confidence: 61%
“…For example, the toxic residues of acrylic SAP-Hs after degradation mark these materials as potential pollutants. This has led to increased concerns regarding the long-term efficiency of acrylic SAP-H soil additives (Bakass et al, 2002;Doumer et al, 2015;Parvathy et al, 2014). However, studies with a focus on the natural detoxification of soil by various plants suggest that degraded SAP-H additives can be considered as a source of nutrients for plants (Raid, 1998).…”
Section: Superabsorbent Hydrogels For Soil Conditioning and Water Manmentioning
confidence: 99%
“…Water adsorption materials have drawn increasing attention recently for their widespread applications in disposable diapers, sanitary napkins, wound dressings, agricultural and horticultural fields as soil conditioners, coal dewatering, surgical pads and matrices for controlled release devices etc. Among the numerous water uptake materials, researchers have focused on superabsorbent polymers, which are hydrophilic and loose networks that are capable of imbibing and retaining a large amount of water and aqueous fluids such as urine, blood, electrolytes etc., ranging from hundreds to thousands of times their own dry weight .…”
Section: Introductionmentioning
confidence: 99%